Haematological findings in dairy cows with concurrent left abomasal displacement and hepatic lipidosis (fatty liver) - KALAITZAKIS, E; PANOUSIS, N; GIADINIS, N; ROUBIES, N; KALDRYMIDOU, E; KARATZIAS, H (Journal of the Hellenic Veterinary Medical Society, 2018)
The main aim of the present field study was to evaluate various haematological parameters in cows with left abomasal displacement (LDA) and concurrent hepatic lipidosis (fatty liver) of different severity. A further objective was to compare these haematological values among animals with concurrent LDA and fatty liver that finally died or recovered. Sixty eight Holstein dairy cows with LDA and 110 control cows were included in the study. Blood and liver biopsy samples were obtained during standing LDA surgery. Liver tissue was examined histologically and classified according to the severity of fatty liver. Haematological analysis and biochemical determination of total lipids and triglycerides concentration of liver tissue were performed. The majority of the haematological parameters evaluated were within normal range. Haematocrit and haemoglobin median values were significantly lower in all LDA cows compared to controls, but no difference was recorded among fatty liver severity groups. Haematological parameters showed no significant difference in animals that finally died compared to the ones that recovered. Haematological parameters were not significantly influenced by the concurrence of LDA and fatty liver in dairy cows.